Development and Assessment of Collagen-Based Biomaterials for Wound Healing Applications - Bileri, Maria Ioanna (My University, 2025)
There is an increasing need for new and effective therapies that can support skin regeneration and improve wound healing. Regenerative medicine is increasingly focusing on the development of bioengineered materials that interact dynamically with the wound microenvironment to enhance the healing process. Among these emerging technologies, collagen-based biomaterials have gained widespread attention due to their inherent biocompatibility, biodegradability, and structural similarity to the extracellular matrix. This study, carried out in collaboration with local biotech SMEs (Promed Bioscience Ltd, Theramir Ltd and RSL Revolutionary Labs), aims to evaluate how formulation, composition, and structural complexity affect the physicochemical and microstructural properties of atelocollagen materials and hydrogels, to identify the best candidates for biomedical use for wound healing. Atelocollagen formulations with different compositions and concentrations (A, D, X3, Combo) were assessed through methods such as measurements of viscosity, osmolality, swelling, dissolution, contact angle, and Scanning Electron Microscopy (SEM) to analyze fibrillar morphology. Hydrogel formulations (T40, T41, T43) based on Combo atelocollagen were tested too. A preliminary in vivo study using the hydrogel was also performed, helping to establish the protocol for future large-scale animal studies. Among the atelocollagen samples, the Combo (a blend of D and X3 atelocollagens) showed the most balanced properties, offering good hydration control and mechanical stability, whereas the A formulation exhibited weak consistency and high dissolvability. Hydrogel T41 exhibits better behavior in terms of swelling stability, suggesting superior moisture retention and compatibility with physiological conditions. The results suggest that changes in the composition of atelocollagen can make a big difference in how it holds moisture, how strong it is, and how well it interacts with biological fluids. These features are essential for supporting wound healing. Combo collagen and T41 hydrogel were identified as the most promising formulations for further development. Preliminary in vivo studies in animal models showed faster and more visible wound healing compared to untreated cases, confirming their potential for skin regeneration applications.
Keywords: wound healing, atelocollagen, hydrogel, physicochemical properties, in vivo testing.